2011
DOI: 10.5194/acp-11-8231-2011
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in understanding physical and chemical properties of African and Asian mineral dust

Abstract: This paper presents a review of recently acquired knowledge on the physico-chemical properties of mineral dust from Africa and Asia based on data presented and discussed during the Third International Dust Workshop, held in Leipzig (Germany) in September 2008. <br></br> Various regional field experiments have been conducted in the last few years, mostly close to source regions or after short-range transport. Although significant progress has been made in characterising the regional variability of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
428
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(489 citation statements)
references
References 262 publications
40
428
4
1
Order By: Relevance
“…Hua dust samples mainly originated from Gobi plants. NO (Formenti et al, 2011;Jöckel et al, 2003;Seinfeld and Pandis, 1998), but the NO − 3 formation is about 10 times faster than that of SO 2− 4 (Rodhe et al, 1981;Vrekoussis et al, 2004Vrekoussis et al, , 2007. Field observation showed that ground surface levels of NO 2 and SO 2 are similar in inland China.…”
Section: Difference In Chemical Composition Between Xi'an and Mt Huamentioning
confidence: 88%
“…Hua dust samples mainly originated from Gobi plants. NO (Formenti et al, 2011;Jöckel et al, 2003;Seinfeld and Pandis, 1998), but the NO − 3 formation is about 10 times faster than that of SO 2− 4 (Rodhe et al, 1981;Vrekoussis et al, 2004Vrekoussis et al, , 2007. Field observation showed that ground surface levels of NO 2 and SO 2 are similar in inland China.…”
Section: Difference In Chemical Composition Between Xi'an and Mt Huamentioning
confidence: 88%
“…The average concentration of Ca 2+ in Category 2 (0.43 ± 0.40 µmol m −3 ) was evidently higher than that in Category 1 (Ca 2+ : 0.17 ± 0.04 µmol m −3 ), implying the probable formation of CaSO 4 and/or Ca(NO 3 ) 2 and the release of NH 3 (gas). Moreover, except for 20080502, the remaining dust samples in Category 2 were transported from the desert relatively enriched with CaCO 3 (1-25 % in wt %) (Formenti et al, 2011). A positive correlation between NO − 3 and SO 2− 4 in Category 2 compared to a negative correlation in Category 1 also implied that the dust particles enriched with CaCO 3 in Category 2 might play an important role to form SO 2− 4 and NO − 3 .…”
Section: Theoretical Analysis Of the Three Categoriesmentioning
confidence: 95%
“…North of the Sahel, all along the western part of the Sahara, there are clusters of many dust sources (Formenti et al, 2011, and the reference therein). Some of these are quite localized but distributed throughout the Western Sahara.…”
Section: Discussionmentioning
confidence: 99%
“…Regions b and c occupy vast regions over northwest Africa. Additional source area is (f) the Bodélé depression, recognized as the most intense dust source in North Africa (Koren et al, 2006;Huang et al, 2010;Formenti et al, 2011) located in the south-central part of the Sahara.…”
Section: Introductionmentioning
confidence: 99%